2017
DOI: 10.3390/su9010125
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Collaboration for Sustainability in the Construction Industry: An Exploratory Study in Italy

Abstract: Abstract:The notion of sustainability, in its three-fold meaning (economic, environmental, and social), is being adopted more and more by companies. Today it is widely accepted that sustainability cannot be achieved by firms in isolation, but requires the collaboration of all supply chain players. This issue is particularly relevant in industrial contexts where the supply chains are complex in terms of structure and number of players, such as the construction industry. Thus, the aim of the paper is to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 94 publications
0
47
0
1
Order By: Relevance
“…Ramanathan et al (2014) in [3] suggested three levels of green collaboration in order to improve sustainability in production, supply and distribution. Additionally, researchers have identified a key factor for successful green collaboration is information sharing, including data relative to strategies and requirements among all supply chain partners [3,27]. However, there is limited evidence, to our knowledge, of collaborative typology identification collecting evidence from more than a single or focal company in the supply chain.…”
Section: Collaboration For Sustainability In the Food Supply Chain (Fsc)mentioning
confidence: 99%
See 4 more Smart Citations
“…Ramanathan et al (2014) in [3] suggested three levels of green collaboration in order to improve sustainability in production, supply and distribution. Additionally, researchers have identified a key factor for successful green collaboration is information sharing, including data relative to strategies and requirements among all supply chain partners [3,27]. However, there is limited evidence, to our knowledge, of collaborative typology identification collecting evidence from more than a single or focal company in the supply chain.…”
Section: Collaboration For Sustainability In the Food Supply Chain (Fsc)mentioning
confidence: 99%
“…Several authors suggest that supply chain collaboration can influence a company's performance [3,6,18,24,25,27]. However, investigation in the FSC in respect of collaboration for sustainability and specifically, analyzing the performance effects of such relationships has been sparsely researched.…”
Section: Research Objectives and Questionsmentioning
confidence: 99%
See 3 more Smart Citations